2020
DOI: 10.3390/ijms21144878
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity Associated with Novel Anticancer Agents (Aflibercept, Dasatinib, Nivolumab): Case Series and Nephrological Considerations

Abstract: Cancer patients have an incidence of about 60% kidney disease development and are at elevated risk of acute renal damage. Kidney disease in these patients is frequently associated with nephrotoxicity from the ongoing oncological treatment. New anticancer therapeutic strategies, such as targeted therapies and immunotherapies, offer substantial benefits in the treatment of many neoplasms. However, their use is associated with significant nephrotoxicity, which qualitatively differs from that seen with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 81 publications
0
14
0
1
Order By: Relevance
“…This study also showed that dasatinib, a multityrosine kinase inhibitor that targets, amongst others, the SRC kinase and PI3K-AKT signalling nodes, can kill senescent cells. Quercetin, a natural flavonoid, also has senolytic activity 183,200,201 . It is not clear how exactly quercetin induces senolysis, but it has been reported that it interferes with the anti apoptotic protein BCL XL through inhibition of upstream pathways including PI3K.…”
Section: ();mentioning
confidence: 99%
“…This study also showed that dasatinib, a multityrosine kinase inhibitor that targets, amongst others, the SRC kinase and PI3K-AKT signalling nodes, can kill senescent cells. Quercetin, a natural flavonoid, also has senolytic activity 183,200,201 . It is not clear how exactly quercetin induces senolysis, but it has been reported that it interferes with the anti apoptotic protein BCL XL through inhibition of upstream pathways including PI3K.…”
Section: ();mentioning
confidence: 99%
“…To date, there is no predictive biomarker of kidney dysfunction for patients receiving these treatments. Creating a database registry for anti-angiogenic therapies and their renal adverse effects could be very helpful [ 169 ]. In the KDIGO (Kidney Disease Improving Global Outcomes) Controversies Conference on onco-nephrology, for patients with CKD, TKIs may be used at a lower-than-standard dose and increased secondarily according to individual tolerability and response [ 160 ].…”
Section: Adverse Effects Of Anti-angiogenic Therapymentioning
confidence: 99%
“…In addition, the VEGF pathway's inhibition can result in hypertension by microvascular rarefaction, and consequently, cause an increase in peripheral resistance, fibrosis, and deficit of podocytes (21). Increased oxidative stress can cause endothelial damage and hypertension, while VEGF prevents the endothelial damage induced by oxidative stress (22).…”
Section: Hypertensionmentioning
confidence: 99%